Teacher Performance Management Oriented to Professional Growth Through Coaching and Mentoring - Didit Darmawan; Agung Maulana; Mohammad Nasiruddin; Abdul Khobir Rahmatullah; Muhammad Iqbal Maududi (Civiliza Publishing, Indonesia., 2026)
This article discusses a teacher performance management model oriented toward professional growth through a coaching and mentoring approach. The purpose of this paper is to describe the design of a teacher performance management model oriented toward professional growth through a coaching and mentoring approach. This research method is based on a qualitative literature review that synthesizes theoretical perspectives on coaching conversations, senior-junior mentoring programs, collaborative academic supervision, and principal competencies as instructional coaches. The results of this study describe how coaching conversations can structure goal setting, classroom reflection, and follow-up planning, while mentoring provides a systematic transmission of pedagogical experience from senior teachers to novice teachers. Collaborative supervision is presented as a bridge between classroom observation and constructive feedback. This article further outlines the organizational and ethical prerequisites for implementing this model, including leadership commitment, time allocation, documentation practices, and a school climate that values ​​openness and shared responsibility for learning. The proposed framework is intended to guide schools in redesigning teacher performance management in a way that strengthens professional identity, improves teaching quality, and fosters a sustainable learning community among educators.